2020
DOI: 10.1155/2020/7806409
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Vinculin as a Potential Diagnostic Biomarker for Acute Aortic Dissection Using Label-Free Proteomics

Abstract: Acute aortic dissection (AAD) is an emergent vascular disease. Currently, its diagnosis depends on clinical and radiological investigations but lacking of serum biomarkers. In this study, we aimed to identify potential serum biomarkers for AAD using label-free proteomics approach. A total of 90 serum samples were collected from three groups: patients with acute aortic dissection (AAD, n=30), patients with acute myocardial infarction (AMI, n=30), and healthy controls (n=30), and the first four samples from each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…The patient cohort is detailed in Table 1 and includes 7 groups with surgically stabilized dissections Type A and B taken into one group, hence 6 groups are shown in the table. The cohort size is in the range of recently published serum proteomic studies, e.g., investigating acute aortic dissection vs. acute myocardial infarction and healthy controls [ 11 ]. The cohort consists of healthy controls; patients with coronary heart disease (CHD) to represent cases with a non-aortic cardiovascular condition; thoracic aortic aneurysms, chronic type B dissections (see also additional information below), acute aortic dissections, and surgically stabilized aortic dissections (Type A and B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The patient cohort is detailed in Table 1 and includes 7 groups with surgically stabilized dissections Type A and B taken into one group, hence 6 groups are shown in the table. The cohort size is in the range of recently published serum proteomic studies, e.g., investigating acute aortic dissection vs. acute myocardial infarction and healthy controls [ 11 ]. The cohort consists of healthy controls; patients with coronary heart disease (CHD) to represent cases with a non-aortic cardiovascular condition; thoracic aortic aneurysms, chronic type B dissections (see also additional information below), acute aortic dissections, and surgically stabilized aortic dissections (Type A and B).…”
Section: Resultsmentioning
confidence: 99%
“…Proteomics using liquid chromatography–tandem mass spectrometry (LC-MS/MS) enables the explorative, quantitative profiling of 100 s of serum or plasma proteins from only a few microliters of liquid biopsy. Previous serum proteome studies in the field of aortic diseases largely focused on comparison of selected aortic diseases vs. a set of controls [ 9 , 10 , 11 , 12 ]. The present study focuses on aortic pathologies including true aneurysms chronic Type B dissections and acute aortic syndromes.…”
Section: Introductionmentioning
confidence: 99%
“…Several promising biomarkers have emerged. Vinculin, lumican, MMP-12 and high levels of ischemia-modified albumin have been considered potential AAD-related serum markers that may assist in the diagnosis and prediction of the in-hospital mortality of patients with AAD (27)(28)(29)(30). However, most of these biomarkers are still clinically unavailable.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we determined proteins that were dramatically up-or downregulated as a biomarker or drug target based on either the FC (such as accession numbers H7C2W5 or B7Z553), proteins with high connectivity (such as protein accession number A0A2R8Y7V5), or both the FC and proteins with high connectivity, indicating that all biomarkers or therapeutic targets were medically effective.. For example, compared with the negative control, the ratio of protein accession numbers A0A2R8Y7V5 and E9PPA5 were signi cantly downregulated; this indicated that they were injured and could not work after MGX treatment, resulting in a better therapeutic effect if the level of injured proteins is increased. A few proteins (Table 2) have been listed as diagnostic biomarkers in other papers such as protein accession number P01034; however, these studies either focused on other diseases (such as acute aortic dissection and not VI), or did not include MGX treatment [15].…”
Section: Discussionmentioning
confidence: 99%
“…Second, although new disease pathways involving the Wnt, ErBb, and BMP signaling pathways were determined, further information such as how they contribute to the pathogenesis of VI remains unclear. Finally, several proteins (Table 2) have been listed as diagnostic biomarkers in other papers such as protein accession number P01034; however, they focused on diseases such as acute aortic dissection, rather than MGX induced VI [15].…”
Section: Discussionmentioning
confidence: 99%